Should more attention be paid to polio sequela cases in China? - Jiancheng Zang; Jiancheng Zang; Longfei Feng; Jichao Wang; Jichao Wang; Xiaonan Wang; Xiaonan Wang; Kun Li; Kun Li; Xiaomei Zhai; Xiaomei Zhai (Frontiers Media S.A., 2023)
Since "Global Polio Eradication Initiative" was launched by World Health Assembly in 1988, the incidence rate of polio has been reduced by more than 99%, and the whole world has entered a post polio era nowadays. China has been a polio free status recognized by World Health Organization for 22 years and most people believe that no more public health concerns need to be given. How is the population of polio survivors in China? What strategies of health economics and actions of public health for those with polio are ethically appropriate? This article, first of all, deeply summarizes and analyzes the history, current situation and unmet needs of population with polio sequelae and post-polio syndrome in China, and then, puts forward important issues faced by polio survivors who natural infected and who due to vaccine associated paralytic polio and vaccine derived poliovirus. The management of polio survivor is not only a medical and rehabilitation problem involving accessibility, accommodations, but also a public health issue, and most importantly, an ethical concern. Furthermore, from the perspective of ethics such as Justice and Cooperation, the author demonstrates the rationality and necessity of continuing to pay more attention to polio sequela cases at this stage in China. Finally, many valuable suggestions and practical recommendations are given.